(untitled) (Research, Society and Development, 2021)
The vegetable species Heliotropium indicum L. (Boraginaceae) is used as poultice to treat inflamed regions of the body, due to its anti-inflammatory and healing properties. Topical formulations have numerous advantages for the treatment of skin lesions, among them stands out the promotion of the local effect of the drug, when its systemic distribution is not desired. Aim: This study aimed to evaluate the rheological behavior and antimicrobial activity of a semi-solid formulation for topical use containing the extract of H. indicum. Metodology: To developed the gel, the formulation was contained by hydroxyethylcellulose (1,5%) and the extract. The formulation was submitted to the preliminary stability study, according to the cosmetic product stability guide (ANVISA), rheological behavior and antimicrobial activity through the disc-diffusion method in solid medium. The formulation was submitted to an oven (45 ± 2 °C) and at room temperature (25 ± 2 °C) to evaluate thermal stress. The readings of the rheological behavior of the gel were measured in increasing and decreasing speed versus shear stress by the apparent viscosity versus shear speed. Results: There was no breakdown of the polymeric gel chain and the formulation showed the behavior of pseudoplastic and thixotropic material, with an antimicrobial activity against strains of Staphylococcus aureus (ATCC 29913), at concentrations of 500 and 250 mg / mL. Conclusion: This formulation remained stable, showing a decrease in apparent viscosity with an increase in shear rate, common in systems containing dispersed polymers and a promising application for the treatment of skin infections.